TLR9-Dependent Activation by Inactivated Parapoxvirus Ovis in Murine Bone Marrow-Derived Dendritic Cells Is Associated with Specific Strain-Dependent Dendritic Cell Subsets - Yanqin Du; Hang Sun; Sonakshi Bhattacharjee; Alexander Birkmann; Ulf Dittmer; Mengji Lu (Karger Publishers, 2024)
Introduction: Inactivated parapoxvirus ovis (iPPVO) exerts strong immunomodulatory effects on innate immune cells, making it an attractive therapeutic candidate. However, little is known about the signaling pathways that are involved in iPPVO-induced immune responses. Methods: In this study, we systematically analyzed how different types of dendritic cells (DCs) react to iPPVO (Zylexis, strain D1701) in both BALB/c and C57BL/6 mice by flow cytometry and ELISAs, and investigated which signaling pathway is related to DC activation by Western blotting and protein profiling. Results: We demonstrated that bone marrow-derived conventional DCs (BM-cDCs) and bone marrow-derived plasmacytoid DCs (BM-pDCs) matured and secreted type I interferons in response to Zylexis stimulation in both mouse strains. Similarly, Zylexis promoted the secretion of IL-12/23p40 and TNF by pDCs. However, IL-12/23p40 and TNF secretion by cDCs were induced in BALB/c mice but not in C57BL/6 mice. Analyzing the underlying signaling pathways revealed that iPPVO-induced maturation of cDCs was Toll-like receptor 9 (TLR9) independent, while the maturation of pDCs partially depended on the TLR9 pathway. Moreover, the production of proinflammatory cytokines by cDCs and the secretion of IFN-α/β by pDCs partially depended on the TLR9 pathway in both mouse strains. Therefore, other signaling pathways seem to participate in the response of DCs to iPPVO, supported by protein profiling. Conclusion: Our data provide useful insights into the diversity of iPPVO sensors and their varying effects across different strains and species.